Potensi Ekstrak Daun Gulma Babadotan (Ageratum conyzoides L.) terhadap Perkecambahan dan Pertumbuhan Paspalum conjugatum Berg. - Mayta Novaliza Isda; Siti Fatonah; Rahmi Fitri (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
The allelopathic substances are an organic agents which produced and released by a plant that cause alteration on the neighboring plants. This research was aimed to determine the effect of Ageratum conyzoides L. leaf extract and also to determine optimum concentration on seed germination and growth of weed Paspalum conjugatum Berg.. This experiment used to extract concentration 0%, 5%, 10%, 15% and 20%. The experiment showed that germination and growth of Paspalum conjugatum Berg.were reduced and to happen damage by leaf extract of Ageratum conyzoides L. The highest germination, growth inhibition and demage at concentrations of the leaf extract 20% respectively are 80.5%, 63.15% dan 17,72 %.